Respostas
respondido por:
18
x/4 - 3 = 4 - x/3
x/4 + x/3 = 4 + 3
x/4 + x/3 = 7 ( mmc de 3 e 4 = 12 , multiplico todos por 12 )
12x/4 + 12x/3 = 12.7
3x + 4x = 12.7
7x = 12 . 7
x = 12 . 7/7
x = 12 ok
x/4 + x/3 = 4 + 3
x/4 + x/3 = 7 ( mmc de 3 e 4 = 12 , multiplico todos por 12 )
12x/4 + 12x/3 = 12.7
3x + 4x = 12.7
7x = 12 . 7
x = 12 . 7/7
x = 12 ok
lelunardi1:
tem certeza dessa resposta???
respondido por:
10
x x
---- - 3 = 4 - -----
4 3 mmc 12
3.x 12.3 12.4 4.x
----- - ------ = ------- - -----
12 12 12 12 elimina-se o denominador
3x - 36 = 48 - 4x
3x + 4x = 48 + 36
7 x = 84
x = 84 / 7
x = 12
---- - 3 = 4 - -----
4 3 mmc 12
3.x 12.3 12.4 4.x
----- - ------ = ------- - -----
12 12 12 12 elimina-se o denominador
3x - 36 = 48 - 4x
3x + 4x = 48 + 36
7 x = 84
x = 84 / 7
x = 12
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás